Slovenian Religiology in the Digital Age - Mari Jože Osredkar (Bogoslovni Vestnik, 2023)
After information about the establishment of the Slovenian Association for the Study of Religions, the article outlines the history of religiology as a science and the beginning of academic religiology in Slovenia. There is a plurality of way of thinking there. Religionologists coming from a theological formation see faith as man’s relationship to transcendence as the heart of every religion. Those who have a sociological formation allow the existence of religion without faith. Concretely, this is reflected in the register of religious communities at the Ministry of Culture of the Republic of Slovenia, where we find many communities that have no connection with faith activity. In the following, the author points out the characteristics of thinking and acting in the digital age: anonymity, irresponsibility, and immediacy of relationship, which affect the current religious practice of individuals and the religious understanding of religion without religion, i.e. without a relationship to the transcendent. In the end, the thesis is that no office, not even a state one, can confirm or give religious identity to individual groups. Interreligious dialogue is the only possible way of recognizing religious identity in communities.